The Histone Methyltransferase G9a Controls Axon Growth by Targeting the RhoA Signaling Pathway - Wilson, Carlos (2020)
The generation of axonal and dendritic domains is critical for brain circuitry assembly and physiology. Negative players, such as the RhoA-Rho coiled-coil-associated protein kinase (ROCK) signaling pathway, restrain axon development and polarization. Surprisingly, the genetic control of neuronal polarity has remained largely unexplored. Here, we report that, in primary cultured neurons, expression of the histone methyltransferase G9a and nuclear translocation of its major splicing isoform (G9a/E10+) peak at the time of axon formation. RNAi suppression of G9a/E10+ or pharmacological blockade of G9a constrains neuronal migration, axon initiation, and the establishment of neuronal polarity in situ and in vitro. Inhibition of G9a function upregulates RhoA-ROCK activity by increasing the expression of Lfc, a guanine nucleotide exchange factor (GEF) for RhoA. Together, these results identify G9a as a player in neuronal polarization.